Ultracompact surface-plasmon-polariton splitter based on modulations of quasicylindrical waves to the total field - Chen, Jianjun; Li, Zhi; Yue, Song; Qihuang Gong (JOURNAL OF APPLIED PHYSICS, 2011)
By coating a metal with a finite-thickness dielectric film, evident differences in the wave-vector magnitude between surface plasmon polaritons (SPPs) and quasicylindrical waves (quasi-CWs) emerge. This brings modulation patterns to the total field on the metal surface near the electromagnetic source. Based on such an effect, an ultracompact SPP splitter with a lateral dimension of only 800 nm is experimentally demonstrated at wavelengths of 740 nm and 832 nm in a dielectric-film-coated asymmetric single nanoslit. These results imply that the additional modulation of quasi-CWs to the total field provide new possibilities for the design of ultracompact plasmonic devices. (C) 2011 American Institute of Physics. [doi:10.1063/1.3564935]